Folic‐Acid‐Functionalized Magnetic Nanoparticles as Green and Magnetic Recyclable Catalyst for the Synthesis of 4‐Aryl‐NH‐1, 2, 3‐triazoles in a Green Media. Issue 40 (5th November 2019) - Bagheri, Sepideh; Nejad, Masoumeh Jadidi; Pazoki, Farzane; Miraki, Maryam Kazemi; Heydari, Akbar
Abstract: A useful, robust, and cheap procedure was obtained for the synthesis of 4‐aryl‐NH‐1, 2, 3‐triazoles via aromatic aldehydes, nitromethane and choline azide in the presence of folic acid immobilized magnetic nanoparticle with good yields. The magnetic catalyst is easily synthesized and can be recycled at least five times with no significant loss in activity. In addition, the choline azide is used as a reagent and green solvent. Abstract : A simple, appropriate, and efficient procedure was gained for the synthesis of 4‐aryl‐NH‐1, 2, 3‐triazoles via aromatic aldehydes, nitromethane and choline azide in the presence of Fe3 O4 @Folic acid nanoparticles. The magnetic catalyst can be recycled at least five times without significant loss of its catalytic activity. Moreover, choline azide as a green and safe solvent was used which proves to be very effective.